Effect of Problem-Based Learning Model with Concept Map on Biology Learning Outcomes and Collaboration Skills - Khusnul Yumni Bulan Sari; Sri Purwati; Jailani Jailani (Bioedukasi: Jurnal Pendidikan Biologi, 2024)
This study aimed to determine the effect of the Problem-Based Learning model with a Concept map on students' biology learning outcomes. This research is a quasi-experimental study with a pretest-posttest control group design. The population used in this study were students of class XI IPA at the SMA Budi Luhur Samarinda. The research sample was taken using the cluster random sampling technique. Data collection techniques of the research used observation and tests. Based on the results of data analysis, the -test with the PBL model on learning outcomes is 0.000 <0.05 it can be interpreted there is an influence of the PBL model with concept maps on biology learning outcomes. The results of the effectiveness of the N-Gain pretest and posttest of the PBL model on student learning outcomes in the control class were 0.47 with a medium category and the experimental class was 0.78 with a high category.. The results of the data analysis presented that students' collaboration increased to the high category (≥ 85.3%) with details of 85.7% indicators of collaborative attitude and character, 84.7% indicators of active collaborating behaviour, and 87.5% indicators of collaboration skills. Based on the t-test with the PBL model for collaboration skills is 0.000 <0.05 it can be interpreted there is an influence of the PBL model with concept maps on collaboration skills. These results arise because of the active role of students in the problem-based learning process so that it is possible for students to gain a more realistic learning experience and improve student learning outcomes as well as student collaboration skills, especially in Biology lessons.